Near-infrared responsive quaternized chitosan-coated MoS2/poly(vinyl alcohol) hydrogel with improved mechanical and rapid antibacterial properties. (5th November 2022) - Yan, Pengfei; Li, Mengya; Liu, Jie; Song, Lingfei; Tang, Keyong
Graphical abstract: Highlights: The QCS-MoS2 /PVA hydrogel exhibited excellent photothermal performance. The hybrid hydrogels exhibited excellent antibacterial properties against S. aureus and E. coli . The synergistic effects of the high temperature and ROS dominated in the antibacterial process. Abstract: Hydrogel is an ideal biomedical material because of its 3D network structure. However, their applications are greatly limited due to their poor mechanical strength and antibacterial property. Herein, a physically cross-linked and light-responsive poly(vinyl alcohol) (PVA) hydrogel embedded with quaternized chitosan-coated molybdenum disulfide (QCS-MoS2 ) nanomaterials was successfully prepared. The photothermal performance of QCS-MoS2 was studied with the results that QCS-MoS2 could be employed as a superior photothermal agent for light responsive hydrogels. After being incorporated with QCS-MoS2, a hydrogen bonding network could be formed in the hydrogel matrix, significantly increasing the mechanical properties. Moreover, the hybrid hydrogels exhibited excellent antibacterial properties. 95.6 % of Staphylococcus aureus ( S. aureus ) and 98.8 % of Escherichia coli ( E. coli ) were killed in 15 min due to the synergistic effects of the high temperature and the reactive oxygen species (ROS) generated by the irradiation of 808 nm near-infrared (NIR) light. No cytotoxicity was found by the introduction of QCS-MoS2, suggesting a great potential in photothermal antibacterial application for biomedical materials.